Why people do the things they do: building on Julius Kuhl’s contributions to the psychology of motivation and volition - Baumann, Nicola; Kazén, Miguel; Quirin, Markus; Koole, Sander Leon (Hogrefe, 2018)
"How can we motivate students, patients, employees, and athletes? What helps us to achieve our goals, improve our well-being, and grow as human beings? Motivation and volition are issues that everyone grapples with in facing the challenges of everyday life: This unique and comprehensive book by leading international researchers takes a genuinely integrative view on motivation and volition from the perspective of personality systems interactions (PSI) theory of Kuhl. After examining the historical trail of the European and American research traditions of motivation and volition and their integration in Kuhl's theory of PSI in the first part of the book, the second part looks in detail at what moves people to action--how needs, goals and motives lead people to choose a course of action (motivation). The third part then explores how people, once they have committed themselves to a course of action, convert their goals and intentions into action (volition). The fourth part of the book shows what an important role personality plays in our motivation and actions. Finally, in keeping with Kurt Lewin's idea that "there is nothing more practical than a good theory," the rich insights of practically applying the integrative theory of motivation and volition are discussed from the perspectives of coaching, training, psychotherapy and education."--